Asymmetry thresholds for common screening tests and their effects on jump performance in professional soccer players - Read, P. J.; McAuliffe, S.; Bishop, C.; Oliver, J. L.; Graham-Smith, P.; Farooq, M. A. (Journal of Athletic Training, 2021)
Context: Arbitrary asymmetry thresholds are regularly used in professional soccer athletes, notwithstanding the sparse literature available to examine their prevalence. Objective: To establish normative and positional asymmetry values for commonly used screening tests and investigate their relationships with jumping performance. Design: Cross-sectional study. Setting: Elite soccer screening. Patients or Other Participants: A total of 203 professional male soccer players. Main Outcome Measure(s): Bilateral and unilateral jumping; range of motion; and hamstrings (HAM), quadriceps (QUAD), and hip-adductor and -abductor strength tests were used to quantify asymmetry. Players were divided into 4 quartiles (Q1-Q4) based on the magnitude of their asymmetry for each test. Single composite scores were also developed to group tests by range of motion and HAM, QUAD, hip-adduction, and hip-abduction strength, and differences in jump performance were examined among players in each quartile. Results: Large variability (range = 5.2%-14.5%) was evident in asymmetry scores across the different tests and physical qualities. Forwards displayed greater asymmetry in concentric quadriceps and eccentric hip-abduction strength (P < .05). The HAM and QUAD composite scores indicated that Q4 players' jumps were shorter than those in other quartiles during a single-legged countermovement jump and 10-second hop (P < .05). No decrements in unilateral jump performance were shown among players in each quartile for range of motion or hip-adduction and -abduction strength, and no composite measures of asymmetry affected bilateral jump performance. Conclusions: No single asymmetry threshold was present for all tests; the outcomes were task, variable, and population specific. Larger asymmetries in HAM and QUAD strength appeared to be detrimental to unilateral jump performance.